Activities of Rain Handlers Reviewing from Islamic Sharia and Traditions - Mohammad Adnan; Badrah Uyuni (Mutawasith: Jurnal Hukum Islam, 2022)
This article discusses rain handlers whose activities are believed to be able to move or stop the rain. The activity of the rain handler has become a tradition that until now is needed not only for activities related to culture but general activities in modern society. By using a qualitative method that uses documents, research results, and observations as data sources which are then analyzed according to social phenomena, it produces an understanding that the rain handler is under a dialectic of magic, religion, and science. This article also mentions the opinions of scholars who are pro and contra regarding this activity. The conclusion is that the law of using the services of a rain handler is not allowed in Islam but it is different from asking a pious or pious person to pray so that it does not rain.